The effect of using some technical clavicles’ according to some biomechanical changes in promwting vertical jump the learning of defeating shot and repelling wall in volley ball - kadhim, widad; shihab, Huda; samir , Luma (Journal of Physical Education, 2012)
The to scholars spoke about the study problem which is represented in the non existane of any progress at the level of the learners despite of the efforts done by teachers and learners in addition of the appearance of boring case arouse during learning perhaps resulted from the need of the learners to avoid classical methods .in learning there are the scholars used the help the of some gymnastic technical devices ,trying to avoid and before of classical way besides knowing the role of these devices in promoting the vertical .jump and developing some bio-mechanical change of the learners than knowing its role in promoting the performance .skillnec the study aimed to know the effect of some tech .gymnastic devices in accorclance of some bio-mechanical changes in promoting the vertical jump and practicing and learn the defeating shot. And the repelling wall in volley boll .the scholars used the experimental concept on asample consist of (20) students of the second .year at college of sport for girls Baghdad university in 2010 – 2011 ,the learning lasted for (6) weeks at average of two units learners weekly.the scholars found out several conclusions the most impotent of then the course in volved with using of gymnastics technical tools which had an active effect in promoting the standard of( defeating shot-repelling well ). The scholars suggested many advices like the necessity of using assisting devices during the learning procedure or the training ,and get the advantage of is available of devices .